Nano-engineering of magnetic particles for bio catalysis and bioseparation - Yu, C; Lo, C; Yeung, C; Tam, K; Tsang, S (2006)
Magnetic nanoparticles encapsulated in a thin coating as magnetic separable nano-vehicle for chemical species is a hot but challenging area. The facilitated separation of a small magnetic body carrying biologically active species is of a tremendous interest however; the stability of the magnetic body remains a key issue. We report new syntheses of silica encapsulated magnetic nanosize particles as magnetic separable carriers in large quantities based on simple synthetic techniques. The major advantage of using nano-size magnetic particles as carriers is that they display an excellent mass transfer coefficient (high surface area to volume ratio) comparable to soluble species but can still be easily separated from liquid using magnetic interaction with an external applied inhomogeneous magnetic field (i.e. 50MGOe). It is shown that the external coating surfaces can isolate and protect the magnetic core from destructive reactions with the environment where a wide range of conditions for fine chemical catalysis can be made possible. The functionalized surfaces could also offer anchoring sites for the immobilization of active chemical species of interests (enzymes, DNA oligos and antibodies). Most of these applications require nanoparticles covered with appropriate surface chemical functionalities where a strong magnetic core is essential for the separation of each particles from solution.